1962
DOI: 10.1161/01.cir.25.3.533
|View full text |Cite
|
Sign up to set email alerts
|

The Pulse Wave Velocity as an Early Indicator of Atherosclerosis in Diabetic Subjects

Abstract: The arterial pulse wave velocity was measured in 87 healthy individuals and in 52 diabetic patients who did not have clinical evidence of atherosclerosis or hypertension. A significant increase in the pulse wave velocity was found in the diabetic subjects. This increase was not correlated with the duration of their illness as judged from clinical history. It is very likely that the high values of pulse wave velocity were indicative of an incipient process of diffuse atherosclerosis and that the measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1
5

Year Published

1967
1967
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(70 citation statements)
references
References 13 publications
5
59
1
5
Order By: Relevance
“…Early methods suggested PWV was faster in type 2 diabetes than in controls. 14,15 As in the present study's baseline data, 16 others reported worse aortic compliance or distensibility in type 2 diabetes than in controls in smaller clinical studies. 17,18 Structural indices such as carotid intima-media thickness also show excess disease in those with diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…Early methods suggested PWV was faster in type 2 diabetes than in controls. 14,15 As in the present study's baseline data, 16 others reported worse aortic compliance or distensibility in type 2 diabetes than in controls in smaller clinical studies. 17,18 Structural indices such as carotid intima-media thickness also show excess disease in those with diabetes.…”
Section: Discussionsupporting
confidence: 67%
“…Based on our observations, it is suggested that cigarette smoking induces endothelial dysfunction in young, healthy subjects, which is characterized by a reduction in FMD and is at least in part reflected by the PWV. The PWV has been established as a non-invasive measure of arterial stiffness and sclerosis (12)(13)(14). The ability of the brachial-ankle PWV to assess peripheral vascular endothelial function has been incompletely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…3,15,16 Changes in arterial stiffness have been observed even at an early stage of disease and in young nondiabetic adults with a family history of type II DM. The prevention of micro-and macroangiopathy requires tight blood glucose control.…”
Section: Discussionmentioning
confidence: 99%